ABC model: A tiered, integrated pathway approach to peri- and post-diagnostic support for families living with dementia (Innovative Practice). (November 2020) - Aldridge, Zena; Burns, Alistair; Harrison Dening, Karen
Services for people with dementia and their families in England are commissioned with a lack of integration and an inconsistent approach creating gaps in service provision. Therefore, families affected by dementia are not receiving the appropriate care in a timely manner and often access support at crisis point. This reactive and crisis driven approach to care is costly financially and can have a negative impact and quality of life of those affected. The ABC model offers an adaptable framework that can inform service provision and improve opportunities to create seamless peri- and post-diagnosis dementia services for families affected by dementia.